KEBIJAKAN PENGENDALIAN RESIKO KESELAMATAN DAN KESEHATAN KERJA PADA TENAGA KERJA (Studi pada Pekerjaan Pengangkatan di Crane Barge Palong III PT. Tanjungpura Balikpapan) - Komeyni Rusba; Hardiyono Hardiyono; Sri Purwanti; Daniel Daniel; Andi Muh Dzul Fadli (Jurnal Public Policy, 2018)
The process of identifying risks and risks is part of policy and risk. Risk control is carried out for efforts to prevent occupational diseases and accidents. To learn about ways to handle risks to the crane barge. This research is a descriptive study, from the time process of this research is a direct research. This research is located at Palong III barge crane PT. Putra Tanjungpura Balikpapan. The method used by researchers in making measurements, information used by companies. In this study, primary data can be used at the same time and direct data that works on location and secondary data obtained from the company. Risk assessment is carried out using the JRA method (Job Risk Assessment and Risk Matrix. In the risk process, finding 12 types of risks, namely 5 risks with low risk levels, 2 risks with moderate levels, 4 risks with risk levels and 1 risk with risk level Things which must be done regularly to achieve different goals, and the results of risks that are effective and efficient. Keywords: Policy, Risk control policy, risk assessment